Pastoralne przesłanie komentarza św. Cezarego z Arles do Apokalipsy św. Jana - Wygralak, Paweł (Vox Patrum, 2018)
The article discusses the commentary of St. Caesarius of Arles on the Apocalypse of St. John. The bishop of Arles wrote his commentary on the basis of the Ticonius’s study. Due to this fact, the work of Caesarius, which has been saved all in one piece, is an extremely important source of information about the commentary of Ticonius and may be very useful in the process of its reconstruction. The explication of the Apocalypse, written by the Gallic shepherd, is practical. The author tried to make comments on the Apocalypse in the context of the situation of the Church in Gaul. He was more interested in ecclesiological message of St. John’s text rather than in its eschatological message. In consequence, the commentary was very practical and might have been used by priests who had to face such problems as the schism of the Church, rebaptism and relations with heretics.